Biological Function of Plant Tannin and Its Application in Animal Health - Tong, Zhenkai; He, Wenfeng; Fan, Xiao; Guo, Aiwei (Frontiers in Veterinary Science, 2022)
Plant tannins are widely found in plants and can be divided into hydrolyzed tannins and condensed tannins. In recent years, researchers have become more and more interested in using tannin-rich plants and plant extracts in ruminant diets to improve the quality of animal products. Some research results show that plant tannins can effectively improve the quality of meat and milk, and enhance the oxidative stability of the product. In this paper, the classification and extraction sources of plant tannins are reviewed, as well as the biological functions of plant tannins in animals. The antioxidant function of plant tannins is discussed, and the influence of their structure on antioxidation is analyzed. The effects of plant tannins against pathogenic bacteria and the mechanism of action are discussed, and the relationship between antibacterial action and antioxidant action is analyzed. The inhibitory effect of plant tannins on many kinds of pathogenic viruses and their action pathways are discussed, as are the antiparasitic properties of plant tannins. The anti-inflammatory action of tannins and its mechanism are analyzed. The function of plant tannins in antidiarrheal action and its influencing factors are discussed. In addition, the effects of plant tannins as feed additives on animals and the influencing factors are reviewed in this paper to provide a reference for further research.